Implementation of the Development of Web-Based Sub-district Integrated Administrative Service Evaluation Model (PATEN) in Sukodono District, Sidoarjo Regency - Tukiman; Diana Hertati; Saifuddin Zuhri (Nusantara Science and Technology Proceedings, 2021)
The quality of public services is very important for the community, as a result of the interaction of aspects, service systems, human resources of service providers, strategies, and customers. The government issued a regulation concerning Peraturan Menteri Dalam Negeri Nomor 4 Tahun 2010 about Integrated District Administration Services (PATEN), as a policy for service delivery at the sub-district level, covering the fields of licensing and non-licensing starting from the application stage to the issuance of documents in one place. This was followed up with the issuance of the Peraturan Bupati Sidoarjo Nomor 78 Tahun 2008 concerning Delegation of Part of the Authority of the Sidoarjo Regent to the Camat, and Peraturan Bupati Sidoarjo Nomor 18 Tahun 2009 concerning. Technical Guidelines for the Implementation of Part of the Regent's authority delegated to the Camat. Then it is also supported by the Peraturan Bupati Sidoarjo Nomor 7 Tahun 2014 concerning Details of Duties, Functions, and Work Procedures of the District in Sidoarjo Regency. To support the government in providing quality public services, several local governments in Indonesia have built e-government systems, built and developed with large budgets and have been successfully implemented, but the level of user acceptance of the system and the level of service quality produced is still low. less than optimal. The purpose of the study was to determine the implementation of a web-based sub-district integrated administration service quality evaluation model (PATEN). The research used is descriptive and qualitative. Data collection is based on interviews and focuses on group discussions. Qualitative data analysis from Miles and Huberman (2014) to analyze the data, consisting of data collection, data condensation, data presentation, and concluding. The results of research in the field prove that the implementation of a web-based integrated service quality evaluation model (PATEN) in the Sukodono Regency Government of Sidoarjo Regency is developing well, adapting according to environmental conditions and changes as well as technology. The quality of public services is very important for the community, as a result of the interaction of aspects, service systems, human resources of service providers, strategies, and customers. The government issued a regulation concerning Peraturan Menteri Dalam Negeri Nomor 4 Tahun 2010 about Integrated District Administration Services (PATEN), as a policy for service delivery at the sub-district level, covering the fields of licensing and non-licensing starting from the application stage to the issuance of documents in one place. This was followed up with the issuance of the Peraturan Bupati Sidoarjo Nomor 78 Tahun 2008 concerning Delegation of Part of the Authority of the Sidoarjo Regent to the Camat, and Peraturan Bupati Sidoarjo Nomor 18 Tahun 2009 concerning. Technical Guidelines for the Implementation of Part of the Regent's authority delegated to the Camat. Then it is also supported by the Peraturan Bupati Sidoarjo Nomor 7 Tahun 2014 concerning Details of Duties, Functions, and Work Procedures of the District in Sidoarjo Regency. To support the government in providing quality public services, several local governments in Indonesia have built e-government systems, built and developed with large budgets and have been successfully implemented, but the level of user acceptance of the system and the level of service quality produced is still low. less than optimal. The purpose of the study was to determine the implementation of a web-based sub-district integrated administration service quality evaluation model (PATEN). The research used is descriptive and qualitative. Data collection is based on interviews and focuses on group discussions. Qualitative data analysis from Miles and Huberman (2014) to analyze the data, consisting of data collection, data condensation, data presentation, and concluding. The results of research in the field prove that the implementation of a web-based integrated service quality evaluation model (PATEN) in the Sukodono Regency Government of Sidoarjo Regency is developing well, adapting according to environmental conditions and changes as well as technology.